2000
DOI: 10.1128/jb.182.13.3854-3857.2000
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Azotobacter vinelandii Nitrogenase-Protective Shethna Protein in Preventing Oxygen-Mediated Cell Death

Abstract: decreased the viable cell number of the mutant further, and the mutant had a slightly higher spontaneous mutation frequency than the wild type in the high-O 2 conditions. Iron starvation conditions, which resulted in fourfold-reduced superoxide dismutase levels, were also highly detrimental to the viability of the protective protein mutants, but these conditions did not affect the viability of the wild-type strain. Nitrogenase or other powerful reductants associated with N 2 fixation may be sources of damaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 17 publications
0
31
0
Order By: Relevance
“…This suggests that high turnover rates of nitrogenase provide active enzyme complexes for N 2 fixation despite the presence of higher intracellular O 2 levels. It is notable that FeS proteins play an important role in Azotobacter vinelandii, possibly by forming a complex with nitrogenase to generate an inactive but oxygen-stable enzyme complex (28,29,49) This process is termed conformational protection, but we could not identify a similar protein in Cyanothece; however, we VOL. 190, 2008 EFFECT OF CONTINUOUS LIGHT ON CYANOTHECE TRANSCRIPTION 3911…”
Section: Discussionmentioning
confidence: 71%
“…This suggests that high turnover rates of nitrogenase provide active enzyme complexes for N 2 fixation despite the presence of higher intracellular O 2 levels. It is notable that FeS proteins play an important role in Azotobacter vinelandii, possibly by forming a complex with nitrogenase to generate an inactive but oxygen-stable enzyme complex (28,29,49) This process is termed conformational protection, but we could not identify a similar protein in Cyanothece; however, we VOL. 190, 2008 EFFECT OF CONTINUOUS LIGHT ON CYANOTHECE TRANSCRIPTION 3911…”
Section: Discussionmentioning
confidence: 71%
“…The iron-sulfur clusters of Azotobacter vinelandii nitrogenase are thought to be shielded during periods of oxygen exposure by Shethna protein (39). In this situation, however, the protected nitrogenase is catalytically inactive, regaining function only when low oxygen levels are restored and the Shethna protein is deactivated.…”
Section: Discussionmentioning
confidence: 99%
“…In this complex, nitrogenase is inactive but transiently protected from damage by oxygen (10,13,21). Additional studies have shown that the function of the FeSII protein is of major importance for cell viability under carbon and/or energy limitation but only when cells are grown diazotrophically (12,14).…”
mentioning
confidence: 99%